A general strategy towards improving the strength and thermal shock resistance of glass-ceramics through microstructure regulation. (1st September 2022) - Feng, Min; Jiang, Chengyang; Chen, Minghui; Zhu, Shenglong; Wang, Fuhui
Highlights: · Crystallization of a SiO2 -Al2 O3 -ZnO-CaO-ZrO2 -TiO2 based glass is controlled by foreign ceramics addition. · Needle-like crystals are retarded from precipitation by Al2 O3 and CeO2 addition. · Al2 O3 addition retards the formation of needle precipitates of Zn2 SiO4 and CaTiSiO5 . · ZrSiO4 precipitation is suppressed by CeO2 addition. Abstract: Glass-ceramics are usually obtained through controlled crystallization. In this work, we propose a new strategy to add an appropriate amount of oxide particles to the parent glass to improve the performance of glass-ceramics. Different amounts of Al2 O3 or/and CeO2 particles were added into a SiO2 -Al2 O3 -ZnO-CaO-ZrO2 -TiO2 based glass, and crystallization behavior, fracture strength, and thermal shock behavior were systematically evaluated. The results indicate that with the addition of Al2 O3 or/and CeO2 particles of moderate amount, the unfavorable needle-like ZrSiO4, Zn2 SiO4, and CaTiSiO5 crystals were largely inhibited when annealed at 900 °C. Accordingly, fracture strength is maintained high after heating at high temperatures. The thermal shock resistance is also enhanced drastically. The additive Al2 O3 is thermodynamically favorable to react with the glass, forming particulate ZnAl2 O4 instead of precipitating the needle-like crystals of Zn2 SiO4 and CaTiSiO5 ; while CeO2 will combine with ZrO2 to form a solid solution and promote the precipitation of primary crystal CaZrTi2 O7 that will not transform to ZrSiO4 with prolonging thermal exposure. Abstract : Image, graphical abstract